Reduction of Oximes and Hydrazones: Asymmetric and Diastereoselective Approaches - Ribeiro, João L.P.; Alves, Cláudia; Cardoso, Ana L.; Lopes, Susana M.M.; Pinho e Melo, Teresa M.V.D. (Current Organic Chemistry, 2021)
The asymmetric reduction of oximes and hydrazones is an attractive and versatile strategy for the synthesis of chiral amines, which are valuable building blocks in organic synthesis. This review summarizes the relevant developments made in the last decade on the enantioselective and diastereoselective reduction of oximes and hydrazones involving metalcatalyzed hydrogenation/hydrogenolysis reactions, hydride donor reactions, and electrochemical reactions.
Keywords: oximes